An Updated Review: Newer Quinazoline Derivatives Under Clinical Trial - ., Abida (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Quinazoline derivatives occupy a distinct and unique place in the medicinal chemistry as they possess diverse biological activities. As on date, about 25 clinically used drugs are quinazoline derivatives. This review has presented a comprehensive detail of quinazoline derivatives which are under clinical trial.